2017
DOI: 10.1016/j.ic.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Undecidability of asynchronous session subtyping

Abstract: Session types are used to describe communication protocols in distributed systems and, as usual in type theories, session subtyping characterizes substitutability of the communicating processes. We investigate the (un)decidability of subtyping for session types in asynchronously communicating systems. We first devise a core undecidable subtyping relation that is obtained by imposing limitations on the structure of types. Then, as a consequence of this initial undecidability result, we show that (differently fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(116 citation statements)
references
References 10 publications
0
116
0
Order By: Relevance
“…Recently, Bravetti et al [10] and Lange and Yoshida [11] have independently shown that asynchronous subtyping (the subtyping relation with output anticipation) is undecidable. In particular, in Bravetti…”
Section: Previous Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Bravetti et al [10] and Lange and Yoshida [11] have independently shown that asynchronous subtyping (the subtyping relation with output anticipation) is undecidable. In particular, in Bravetti…”
Section: Previous Resultsmentioning
confidence: 99%
“…The aim of this paper is to detect significant decidable fragments of asynchronous session subtyping and to establish a more precise boundary between decidability and undecidability. In particular, concerning decidability, as discussed above, the few decidable fragments of asynchronous subtyping known so far are extremely restrictive: our relations < < sin , < < sout [10] and the decidable relations considered by Lange and Yoshida [11]. Here, for the first time, we show decidability of a fragment that does not impose any limitation on communication buffers and allows both the subtype and the supertype to include multiple choices (either for input branchings or for output selections), thus opening the possibility for some practical applicability in restricted specific scenarios (e.g.…”
Section: Contributed Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We expect the compatibility could be extended, since the subtyping for asynchronous multiparty sessions is more permissive than the subtyping for the synchronous ones [25]. Of course this extension requires care, being the subtyping of [25] undecidable, as shown in [2,24].…”
Section: Future Work and Conclusionmentioning
confidence: 99%